Realization of auxiliary management and control channel in WDM-PON based on DBPSK re-modulation and delay interferometer detection - Bin LUO; Yong LIU; Jizhao LU; Rui GONG; Hongyu YANG; Qiushi YUAN (Dianxin kexue)
In WDM-PON,the OAM data path and user data path were independent in the TC layer.The OAM data could be transmitted either transparently or by codec.Specifically,the transparent mode was preferred by the industry network due to the free of codec and low latency.Different from the existing transparent modes,such as base-band re-modulation and RF band,a novel method for the realization of auxiliary management and control channel was proposed,which was based on the DBPSK re-modulation and delay interferometer detection.Since the OAM data was re-modulated on the phase of user data,which was modulated intensively,it would not take any impact on the quality of user data.But,in both base-band re-modulation and RF band methods,the re-modulation of OAM data would introduce interference to the user data,which was not allowed in the demanding industry network.The proposed method is thought promising as one of the solutions for auxiliary management and control channel in WDM-PON.